2012
DOI: 10.1134/s1027451012040180
|View full text |Cite
|
Sign up to set email alerts
|

Structural phase changes in a titanium-silicon system modified by high-current electron beams and compression plasma flows

Abstract: Structural phase changes in a titanium-silicon system treated by low energy high current elec tron beams (HCEBs) and compression plasma flows (CPFs) with the duration 100 µs and the energy density 12-15 J/cm 2 are studied. Scanning electron microscopy, X ray diffraction and electron microprobe analysis are used in this work. The formation of a titanium doped silicon layer 10-25 µm thick, titanium silicides (TiSi 2 under HCEBs and Ti 5 Si 3 under CPF treatment), silicon dendrites, and needle like eutectics (typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…In addition, a high cooling rate (~10 7 K/s) and a maximum temperature gradient (~10 7 K/m) were estimated. However, an investigation on Ti-Si system under CPF treatment [20], confirmed that, under the impact of anuniform heat flux (without convection), the melting process starts at the threshold energy density 12 J/cm also showed that by doubling the energy density, the thickness of the molten alloy layer becomes 15 times thicker. It should be mentioned that the calorimetric experiment gives the average value of the energy density, and because of the inhomogeneity of the heat flux, the density of the plasma energy in local areas may be much greater than calculated values.…”
Section: Simulation Of Temperature Distributionmentioning
confidence: 95%
See 1 more Smart Citation
“…In addition, a high cooling rate (~10 7 K/s) and a maximum temperature gradient (~10 7 K/m) were estimated. However, an investigation on Ti-Si system under CPF treatment [20], confirmed that, under the impact of anuniform heat flux (without convection), the melting process starts at the threshold energy density 12 J/cm also showed that by doubling the energy density, the thickness of the molten alloy layer becomes 15 times thicker. It should be mentioned that the calorimetric experiment gives the average value of the energy density, and because of the inhomogeneity of the heat flux, the density of the plasma energy in local areas may be much greater than calculated values.…”
Section: Simulation Of Temperature Distributionmentioning
confidence: 95%
“…Thermal, mechanical, and radiation effects of CPF pulses provide nonequilibrium conditions for structural and phase transformations and the formation of novel low-dimensional structures in the surface layers of solids. CPF treatment of a thin metal layer (e.g., Fe, Ti, Ni, Zr, Mo) on a silicon substrate successfully made it possible to form metal silicides in the near-surface layer [16,[19][20][21].…”
Section: Introductionmentioning
confidence: 99%